The effects of creatine supplementation on cognitive function in adults: a systematic review and meta-analysis - Xu Chen; Siyuan Bi; Wenxin Zhang; Lin Luo (2024)
This study aimed to evaluate the effects of creatine monohydrate supplementation on cognitive function in adults and explore its potential role in preventing and delaying cognitive impairment-related diseases.